APROVECHAMIENTOS DE RECURSOS HIDRICOS EN MISIONES. BOMBA DE ARIETE HIDRAULICO - Javier, Kerkhoff A.; Barney, Erik; Leandro, Corrado; Marco, Barbaro; Hugo, Yacowek; Nestor, Chak (Salão do Conhecimento, 2013)
Resumo